1996
DOI: 10.1558/ijsll.v3i1.39
|View full text |Cite
|
Sign up to set email alerts
|

Identical twins, different voices

Abstract: The differences between voices are often broadly categorized as either 'organic' or 'learned', implying that some are determined by our anatomical inheritance, and others by what we copy from people around us or choose in order to mark our individuality. It is normally impossible, however, to assign observable differences to one source or the other, since neither source is experimentally controllable. In the case of identical twins, nature provides such a control. It can reasonably be assumed that the anatomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 0 publications
6
30
0
Order By: Relevance
“…We find that the amplitude of twin B is higher than twin A from Nolan and Oh (1996), the learning also is the main reason that leads to the difference of voice between identical twins. This helps speaker recognition in twin identification.…”
Section: Discussionmentioning
confidence: 68%
“…We find that the amplitude of twin B is higher than twin A from Nolan and Oh (1996), the learning also is the main reason that leads to the difference of voice between identical twins. This helps speaker recognition in twin identification.…”
Section: Discussionmentioning
confidence: 68%
“…Thus dynamic parameters might be influenced more by physiological properties. In addition, other studies have found that MZ twins were remarkably similar in dynamic coarticulatory patterns (Whiteside and Rixon, 2003;Nolan and Oh, 1996).…”
Section: A Twins' Speechmentioning
confidence: 85%
“…However, speaker-specific characteristics of normal speech are a less frequent research topic (see Loakes, 2006, p. 41). Acoustic and perceptual studies on twins' speech have shown that MZ twins are more similar than same-sex DZ twins or age-matched siblings in their acoustic output: E.g., mean F0 (Przybyla et al, 1992;Debruyne et al, 2002), voice quality parameters (van Lierde et al, 2005) and coarticulatory patterns (Nolan and Oh, 1996;Whiteside and Rixon, 2003). While it seems to be very difficult for unfamiliar listeners to distinguish MZ and DZ twins by listening to just one word (Weirich and Lancia, 2011), even MZ twins can be distinguished in perception tests with familiar listeners (Whiteside and Rixon, 2000) and in acoustic analysis on formant patterns (Loakes, 2006) or by using automatic speaker recognition systems (K€ unzel, 2010).…”
Section: A Twins' Speechmentioning
confidence: 99%
“…Many dimensions of speaker-specific behaviour relate to linguistic structure and linguistic categories, but in ways that cannot be captured if speech is considered solely in terms of an inventory of phonemes and major intonational categories� Rather, there are dimensions of speaker-specific behaviour that involve phonetic detail� As defined by (among others) Local (2003) and Hawkins (Hawkins and Smith, 2001;Hawkins, 2003Hawkins, , 2010, phonetic detail refers to phonetic information that affects people's responses but "is not considered a major, usually local, perceptual cue for phonemic contrasts in the citation forms of lexical items" (Hawkins and Local, 2007: 181)� This type of information is "systematically distributed [according to linguistic/communicative function] but not systematically treated in conventional approaches" (ibid. )� Thus, phonetic detail refers not to information that mainly distinguishes phonemes (such as /pa/ vs� /ba/), but to cues that distinguish other aspects of linguistic structure, such as prosodic structure (compare the unstressed /p/ in potato with the stressed /p/ in important); syllabic and morphological structure (/p/ is more heavily aspirated in the morphologically-complex word displease than in the mono-morphemic word displays; Smith et al�, 2012); or pragmatic function (for Standard Southern British English, both [pʰ] and [p'] are possible allophones of /p/ in it's a tap, but the ejective sounds more emphatic, definite, and final than the aspirated stop� The range of aspects of linguistic structure that condition systematic variation in phonetic detail is extensive� Crucially for the present purposes, there is evidence of speaker-specific variation in many of them, henceforth termed speaker-specific phonetic detail (SSPD)� For example, speakers vary in the extent to which they coarticulate, and in the precise coarticulatory strategies that they use� Reviewing research in this area, Kühnert and Nolan (1999) comment that it is relatively scarce, and that "the high variability found in the data makes it difficult to distinguish between effects which should be considered as being idiosyncratic and effects which simply reflect the allowed range of variation for the phenomenon"� Nonetheless, they identify several experiments showing individual coarticulatory differences: among British English speakers in coarticulation of /r/ and /l/ with a following vowel (Nolan, 1983(Nolan, , 1985, and among both Swedish (Lubker and Gay, 1982) and English speakers (Perkell and Matthies, 1992) in the timing of movements for anticipatory lip rounding� Some of this variation may be due to an individual's genetic (anatomical and physiological) inheritance, as suggested by Weirich et al�'s (2013) finding that tongue looping trajectories are more similar in monozygotic twins than in dizygotic twins or unrelated speakers (though see Nolan and Oh, 1996 for a demonstration of articulatory variability within identical twin pairs)� Speakers also vary in their "prosodic signatures", i� e� the detailed phonetic means they use to index prosodic prominence and prosodic bound-aries� With respect to prominence, individual speakers mark prominent as opposed to non-promi...…”
Section: Speaker-specific Phonetic Detail (Sspd)mentioning
confidence: 99%